Evaluation of SARS-CoV-2 seroprevalence among clinical laboratory workers and its association with past exposure to infection and vaccination - Humaira Ahmed; Sahar Iqbal; Syed Talha Naeem; Uzma Bukhari; Fouzia Zeeshan (LIAQUAT MEDICAL RESEARCH JOURNAL, 2024)
The pandemic of COVID-19, due to the SARS-CoV-2 virus, has significantly impacted global health. Understanding the dynamics of immunity, both natural and vaccine-induced, is crucial for public health strategies. The study aimed to determine the seroprevalence of SARS-CoV-2 antibodies among clinical laboratory workers and its relationship with previous exposure to infection and vaccination. This was a prospective observational study conducted at the chemical Pathology section of Dow Diagnostic Research and Reference Laboratory (DDRRL), Dow University of Health Sciences, Karachi, Sindh, Pakistan from 1st January to 30th December 2021. Following ethical approval, 80 clinical laboratory workers provided informed consent to participate. Blood samples were collected and tested for SARS-CoV-2 IgG antibodies. The baseline demographic and clinical information was recorded, and conducted follow-up antibody tests six months later. The mean age of the participants was 37.7 years, with a standard deviation of 9.42. There were 46 males (57.5%) and 34 females (42.5%) in the study. Half of the participants (50%) had been vaccinated, with 35% receiving a single dose and 15% receiving both doses. 71.3% of the participants had comorbidities. SARS-CoV-2 antibodies were found to be reactive in 50% of the participants. The study also found significant associations between antibody presence and prior COVID-19 infection, vaccination status, contact history with COVID-19 patients, and prior history of hospitalization (p < 0.05). The study compared the initial and post-booster antibody levels among three groups of subjects (vaccinated, vaccinated with no prior COVID-19 infection, and non-vaccinated with prior COVID-19 infection), and found that antibody levels were significantly high in vaccinated subjects and non-vaccinated subjects with prior COVID-19 infection (p-value < 0.05). A significant difference was observed in antibody titers among subjects with prior history of vaccination and COVID-19 infection. In conclusion both natural infection and vaccination may induce antibodies against SARS-CoV-2 infection.